Comparison of Motor Proficiency and Functional Ambulation in Duchenne Muscular Dystrophy With Healthy Peers - Yıldız, Şulenur; Şahin, Sedef; Bulut, Numan; Tunca Yılmaz, Öznur; Karaduman, Aynur Ayşe; AKEL, BURCU SEMİN (Taylor & Francis Ltd., 2020)
Aims:The study was aimed to investigate the difference between boys with Duchenne muscular dystrophy (DMD) and healthy peers in terms of gross and fine motor proficiency, and determine the relationship between motor proficiency and ambulation. Methods:A total of 24 boys with DMD and 22 healthy peers were evaluated. Demographics and physical characteristics were recorded. The Bruininks Oseretsky Test of Motor Proficiency-Short Form (BOTMP-SF) was administered to evaluate gross and fine motor proficiency in both groups. The 6-minute walk test (6MWT) was performed to evaluate functional walking capacity and North Star Ambulatory Assessment (NSAA) was used to determine ambulatory status of boys with DMD. Results:The gross motor proficiency score was significantly lower in boys with DMD (p = 0.001). No difference was found between the groups in terms of fine motor proficiency (p = 0.962). The gross motor function of BOTMP-SF was significantly related to 6MWT distance (r = 0.696,p = 0.001) and NSAA (r = 0.738,p = 0.001). No relationship was found between BOTMP-SF fine motor proficiency and 6MWT distance (r = 0.210,p = 0.361), and NSAA (r= -0.020,p = 0.928). There were significant correlations between running speed and agility with 6MWT distance (r = 0.585,p = 0.005) and NSAA (r = 0.650,p = 0.056). Conclusions:Boys with DMD were more affected in aspects of gross motor proficiency than healthy peers, while fine motor proficiency were found same. The gross motor proficiency was found more related to the level of ambulation.
Keywords: Child; Duchenne; Functional Performance; Motor Skills; Muscular Dystrophy; Walking